المسؤولیة الاجتماعیة كخیار فعال لاستدامة المؤسسات الصغیرة والمتوسطة في الجزائر - gasmi, said; arbia, saloua; belaid, ouarda (Finance and Business Economies Review, 2017)
The aim of this paper is to discover the role played by the adoption of the concept of social responsibility in achieving the sustainability of small and medium enterprises in Algeria. The small and medium enterprises in Algeria face many obstacles, the most important of which are financing, administrative, marketing, etc., All of these factors make its sustainability as difficult issue. Therefore, the search for new and developed management concepts to deal with complex environmental variables is one of the basic requirements and objectives of each organization seeking efficiency and effectiveness. To maintain its survival and continuity, so this research was to analyze the relationship between the two variables more (social responsibility, sustainability of small and medium enterprises), where we dealt with the three basic sections are: First: theoretical concepts about small and medium enterprises; Second: the most important social responsibility programs at the level of economic enterprises; Third, the role of adopting the concept of social responsibility in achieving sustainability of small and medium enterprises in Algeria